FBXO38 Ubiquitin Ligase Controls Centromere Integrity via ZXDA/B Stability - Dibus, Nikol; Korinek, Vladimir; Cermak, Lukas (Frontiers in Cell and Developmental Biology, 2022)
Alterations in the gene encoding the E3 ubiquitin ligase substrate receptor FBXO38 have been associated with several diseases, including early-onset motor neuronopathy. However, the cellular processes affected by the enzymatic action of FBXO38 are not yet known. Here, we identify the zinc finger proteins ZXDA/B as its interaction partners. FBXO38 controls the stability of ZXDA/B proteins via ubiquitination and proteasome-dependent degradation. We show that ZXDA/B proteins associate with the centromeric protein CENP-B and that the interaction between ZXDA/B and FBXO38 or CENP-B is mutually exclusive. Functionally, ZXDA/B factors control the protein level of chromatin-associated CENP-B. Furthermore, their inappropriate stabilization leads to upregulation of CENP-A and CENP-B positive centromeric chromatin. Thus we demonstrate a previously unknown role of cullin-dependent protein degradation in the control of centromeric chromatin integrity.